Physiological acclimation to drought stress in Solidago canadensis. Issue 4 (3rd October 2013) - Nolf, Markus; Pagitz, Konrad; Mayr, Stefan
Abstract Solidago canadensis is an invasive species from North America that is spreading across Europe, Australia and temperate Asia. We hypothesized that the species' wide ecological amplitude is also based on its potential in hydraulic acclimation, and analyzed hydraulic and anatomical properties along a transect with decreasing soil humidity. Stem hydraulic conductivity, vulnerability to drought‐induced embolism, stomatal closure during dehydration and xylem‐anatomical parameters were quantified at three sites. At the humid site, specific hydraulic conductivity of stems (1.0 ± 0.2 kg m–1 MPa–1 s–1) was about twofold higher, and leaf‐specific conductivity about 1.5 times higher (3.1 ± 0.5 kg m–1 MPa–1 s–1) than at the dry site. Water potential (Ψ) at 50% loss of conductivity was −3.7 ± 0.1 MPa at the dry site and −3.1 ± 0.2 MPa at the humid site (September). Vulnerability to drought‐induced embolism decreased along the transect and over the vegetation period. At drier sites, stomata started closing at lower Ψ while complete stomatal closure was reached at less negative Ψ (12% of maximum stomatal conductance: –2.5 ± 0.0 and −3.0 ± 0.2 MPa at the dry and humid site). The safety margin between stomatal closure and 50% loss of conductivity was 1.2 and 0.2 MPa at the dry and humid sites. The observed variability indicated an efficient acclimation in hydraulic conductivity and safety: plants at dry sites exhibited lower specific hydraulic conductivity, higher embolism resistance and broader safety margins, signifying a trade‐off between the hydraulic safety and efficiency. The observed intraspecific plasticity in hydraulic and anatomical traits may help to explain the invasive potential of this species.